MODEL ATAU METODE UNTUK MENINGKATKAN KUALITAS PERKULIAHAN ANALISIS REAL: STUDI LITERATUR : Model Or Methods For Improving The Quality Of Real Analysis Lectures: Literature Study - Nasution, Afifah Nabila; Hasanah, Rusi Ulfa; Ningsih, Sri Rahayu; Sastika, Weni (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2024)
Real analysis is an important subject in college level mathematics education. The quality of real analysis lectures can influence students' understanding of basic concepts in advanced mathematics. This literature study aims to develop a model that can improve the quality of real analysis lectures through a review of various related literature sources. The method used in this study is a literature review, where various literature sources relevant to the research topic are analyzed thoroughly. The results of the analysis show that efforts that can be made to improve the quality of real analysis lectures include applying the lesson study method, developing relevant and quality textbooks, as well as providing support from family and social circles for students. The conclusion of this study confirms that the application of lesson study in the context of real analysis lectures can provide significant benefits in improving the quality of learning. Apart from that, developing textbooks that suit student needs is also an important step in increasing the effectiveness of lectures. Support from family and social environment also plays a crucial role in creating a conducive learning environment for students.